2010
DOI: 10.2176/nmc.50.966
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Aggressive Blood Pressure Lowering on Hematoma Enlargement in Patients With Ultra-acute Intracerebral Hemorrhage

Abstract: The preventive effect of aggressive blood pressure lowering on hematoma enlargement was investigated in patients with ultra-acute spontaneous intracerebral hemorrhage (ICH). Retrospective review of 248 patients (145 males, 103 females) with spontaneous ICH treated in our hospital between 2005 and 2008 identified patients with ultra-acute ICH who were directly taken to our institute by ambulance within 3 hours after onset. Patients who could not be assessed twice by computed tomography (CT) within 24 hours afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Stroke is one of the leading causes of death and disability worldwide. 1 – 3 Decreasing the time from stroke onset to hospital arrival offers the greatest opportunity for effective acute stroke therapy 4 8 ; however, delay in hospital presentation of patients with acute stroke still remains substantial. 9 12 …”
Section: Introductionmentioning
confidence: 99%
“…Stroke is one of the leading causes of death and disability worldwide. 1 – 3 Decreasing the time from stroke onset to hospital arrival offers the greatest opportunity for effective acute stroke therapy 4 8 ; however, delay in hospital presentation of patients with acute stroke still remains substantial. 9 12 …”
Section: Introductionmentioning
confidence: 99%
“…For example, Nishikawa et al demonstrated that early BP treatment to < 140 mm Hg was associated with low rates of hematoma expansion to only 15%. 34 This was complemented by several studies that showed that early treatment of elevated BP was associated with a decrease in mortality and poor outcome. [35][36][37][38][39][40] On the contrary, Qureshi 41 showed that a rapid decline in BP within 24 hours from ICH onset was associated with a rise in mortality.…”
Section: Evidence From Observational and Pilot Studiesmentioning
confidence: 97%